Arthrofibrosis and large joint scarring. (2nd January 2019) - Chen, Antonia F.; Lee, Yong Seuk; Seidl, Adam J.; Abboud, Joseph A.
ABSTRACT: Large joint arthrofibrosis and scarring, involving the shoulder, elbow, hip, and knee, can result in the loss of function and immobility. The pathway of joint contracture formation is still being elucidated and is due to aberrations in collagen synthesis and misorientation of collagen fibrils. Novel antibodies are being developed to prevent arthrofibrosis, and current treatment methods for arthrofibrosis include medical, physical, and surgical treatments. This article describes the biology of joint contracture formation, along with current and future pharmacologic, biologic, and medical interventions.